Efficient Separation of Hydroxylamine from Metal Ions by PIM-ED Process - Lilei Yang; Zhongwei Ding; Zhengtao Zhu; Weidong Zhang (Separations)
Selective separation of hydroxylamine (HA) from metal ions to prepare high-purity HA remains a challenge. In this study, given that HA can react with carbonyl compounds, TTA (thenoyltrifluoroacetone) was screened as a carrier to prepare the polymer inclusion membrane (PIM), which was used to separate HA from metal and inorganic acid ions. The experimental results demonstrated that the PIM exhibited good selectivity for HA. During the PIM process, the proton gradient served as a driving force to transport NH2OH(I). The electrodialysis (ED) process was used to efficiently and continuously provide proton gradient without introducing other ions, which coupled with PIM to separate HA. Under the optimum conditions, the separation factors of NH2OH(I)/Na(I) and NH2OH(I)/K(I) were 30.81 and 35.11; the purity of HA was 99.4%, indicating that the PIM-ED process can be used for high-purity preparation of HA.